# (9x-1)(2x+9)=0

## Simple and best practice solution for (9x-1)(2x+9)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (9x-1)(2x+9)=0 equation:

Simplifying (9x + -1)(2x + 9) = 0 Reorder the terms: (-1 + 9x)(2x + 9) = 0 Reorder the terms: (-1 + 9x)(9 + 2x) = 0 Multiply (-1 + 9x) * (9 + 2x) (-1(9 + 2x) + 9x * (9 + 2x)) = 0 ((9 * -1 + 2x * -1) + 9x * (9 + 2x)) = 0 ((-9 + -2x) + 9x * (9 + 2x)) = 0 (-9 + -2x + (9 * 9x + 2x * 9x)) = 0 (-9 + -2x + (81x + 18x^{2})) = 0 Combine like terms: -2x + 81x = 79x (-9 + 79x + 18x^{2}) = 0 Solving -9 + 79x + 18x^{2}= 0 Solving for variable 'x'. Factor a trinomial. (-9 + -2x)(1 + -9x) = 0## Subproblem 1

Set the factor '(-9 + -2x)' equal to zero and attempt to solve: Simplifying -9 + -2x = 0 Solving -9 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -2x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -2x = 0 + 9 -2x = 0 + 9 Combine like terms: 0 + 9 = 9 -2x = 9 Divide each side by '-2'. x = -4.5 Simplifying x = -4.5## Subproblem 2

Set the factor '(1 + -9x)' equal to zero and attempt to solve: Simplifying 1 + -9x = 0 Solving 1 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -9x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -9x = 0 + -1 -9x = 0 + -1 Combine like terms: 0 + -1 = -1 -9x = -1 Divide each side by '-9'. x = 0.1111111111 Simplifying x = 0.1111111111## Solution

x = {-4.5, 0.1111111111}

### See similar equations:

| 26=x-12 | | -4x^2+16=0 | | 4y-3(y+8)=12 | | 2L*2-3=12 | | x+8x+9x= | | 5+x=7 | | 100-4x=2x+22 | | 3b=45 | | 5(3x-4)=2(5x+20) | | -2[y-4]=12-y | | -20(-31)= | | 2(y-12)+2y=-84 | | 7b+5b= | | 2x+14=-41-9x | | 11x-(6x+6)=19 | | 4x^2=26x-30 | | -2x^2+128=0 | | -90-9x=9x+18 | | 6(x-5)=5(x+5) | | 15x^3+44x^2+11x-6=0 | | -5(x+37)= | | 8x=64 | | -2w+5=26+w | | 11-9x=87-37x | | 3t+8t+3t+3t= | | 5(y+2)+3y=50 | | 5xn-3=32 | | c^2=25 | | 25x^2-49=0 | | -2(y-4)=12-y | | 284-2x=43x+19 | | 8b-11+3b=121 | | 25=4+3y | | 3x^2=51x | | 12x-3=4x+93 | | 3(2x-10)=6(x-10) | | 2(x-3)=6.5 | | 9y+y+8y+2y+5y= | | 7x-3x-8=24 | | 2(x-3)+4x=6.5 | | 5y-5=-35 | | 2(x-3)+4x=18 | | 9a-4+3a-33=23 | | 10(x-5)=9(x+5) | | 12=2w+2 | | 2(8q-1)+3(5q+6)= | | 3(n-1)-2=4(n-4)-(n-11) | | 3(6x-4)=22x | | 3x+10=45-2x | | 2x^2-7x-16=-3x | | 3g+3(-5+4g)=1-g | | 15y=14(y+16) | | 4j-1+7= | | 2-6x=10-8x | | -17=-5+4u | | 3(1+Y)=3-(5y+2) | | 2x+3(x-1)=27 | | 139-3x=6x+22 | | 11-10x=103-38x | | 49-2x=7x+16 | | 4x-8=x+25 | | 118-(3xb)= | | 4(x+7.50)=40 | | 6f+30=2f-8 | | 4a-2=7a-6 |